Peran Pendidikan Agama Islam dalam Membangun Masyarakat Berdaya: Refleksi Pengajaran Pemberdayaan Masyarakat pada Program PPL di Universitas Sunan Giri Surabaya - Ahmad Murtadlo; Ely Masnawati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic Religious Education (PAI) holds a strategic role in fostering a society that is not only intelligent but also empowered and virtuous. This article reflects on my experience during the Field Practice Program (PPL) at Sunan Giri University, Surabaya, where I taught Community Empowerment to undergraduate students. The purpose of this teaching was to provide an understanding that community empowerment encompasses strengthening moral and spiritual aspects derived from Islamic values, in addition to economic dimensions. The impact of incorporating Islamic Religious Education values into the community empowerment process was evaluated through a reflective approach. The reflections indicate that integrating Islamic Religious Education into community empowerment teaching helps students become more aware of their vital role in building an independent, honest, and dignified society. Interactive discussions and mosque-based case studies proved effective in fostering student engagement and motivating them to apply empowerment concepts within their communities. Despite challenges such as the varying initial understanding of students, a locally contextualized approach successfully enhanced the learning effectiveness. In conclusion, Islamic Religious Education has a strategic contribution in shaping an empowered generation capable of becoming agents of social change through an Islamic ethical approach. Developing a more practical curriculum and fostering collaboration with communities are necessary to strengthen the implementation of empowerment based on Islamic values.